1996
DOI: 10.1074/jbc.271.36.21793
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B and H2O2 Are Potent Inducers of Vascular Endothelial Growth Factor Expression in Cultured Keratinocytes

Abstract: Vascular endothelial growth factor (VEGF), also known as vascular permeability factor, is strongly expressed by epidermal keratinocytes during wound healing, in psoriasis, and in bullous diseases such as erythema multiforme and bullous pemphigoid. All of these disorders are characterized by increased microvascular permeability and angiogenesis. Since the development of erythema as a result of hyperpermeable blood vessels is also a common feature after excess sun exposure, we speculated about an up-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
110
1
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 41 publications
11
110
1
8
Order By: Relevance
“…ROS generally promote activation of HIF [41][42][43][44][45][46][47] and consistent with this, we demonstrated that NAC and catalase decreased induction of HIF activity in hypoxic conditions. However, only NAC, which contains a free thiol, reversed the ability of PEITC to inhibit HIF activity, whereas the non-thiol based antioxidants catalase and Trolox either had no effect, or enhanced the inhibitory effects of PEITC.…”
Section: Peitc Does Not Alter Expression Of Hif1 Rnasupporting
confidence: 63%
See 1 more Smart Citation
“…ROS generally promote activation of HIF [41][42][43][44][45][46][47] and consistent with this, we demonstrated that NAC and catalase decreased induction of HIF activity in hypoxic conditions. However, only NAC, which contains a free thiol, reversed the ability of PEITC to inhibit HIF activity, whereas the non-thiol based antioxidants catalase and Trolox either had no effect, or enhanced the inhibitory effects of PEITC.…”
Section: Peitc Does Not Alter Expression Of Hif1 Rnasupporting
confidence: 63%
“…Treatment of cells with hydrogen peroxide is sufficient to stabilise HIF1α and induce expression of HIF target genes, even in normoxia [41]. Moreover, HIF activation in normoxia and hypoxia is inhibited by antioxidants such as GSH, its metabolic precursor N- …”
mentioning
confidence: 99%
“…H 2 O 2 increased VEGF expression in keratinocytes [37] and in endothelial cells [38]. We have previously shown that psoriasin is induced by stress stimuli such as ROS [13].…”
Section: Discussionmentioning
confidence: 91%
“…Expression of VEGF is known to be regulated by other mediators, including platelet-derived growth factor (35), TGF-␤ (36), IL-1 (28), oxygen radicals and nitric oxide (30,(37)(38)(39), and hypoxia (32,38,40). The synovium is chronically hypoxic in RA and probably also in CIA: biochemical evidence of anaerobic metabolism suggests that blood flow is insufficient to meet the high metabolic demands of inflamed synovial tissue (41).…”
Section: Discussionmentioning
confidence: 99%